2017
DOI: 10.7812/tpp/16-055
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Discussing Childhood Trauma in Primary Care

Abstract: Context: Exposure to traumatic events is common in primary care patients, yet health care professionals may be hesitant to assess and address the impact of childhood trauma in their patients.Objective: To assess patient preferences for discussing traumatic experiences and posttraumatic stress disorder (PTSD) with clinicians in underserved, predominantly Latino primary care patients.Design: Cross-sectional study. Main Outcome Measure:We evaluated patients with a questionnaire assessing comfort to discuss trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…22 Patients are willing to discuss trauma exposure and believe their clinicians will be able to provide assistance in a sensitive manner. 20 Education and training on ACE screening can mitigate clinician discomfort, a sentiment echoed throughout the studies included in this review.…”
Section: Implementation Of Ace Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Patients are willing to discuss trauma exposure and believe their clinicians will be able to provide assistance in a sensitive manner. 20 Education and training on ACE screening can mitigate clinician discomfort, a sentiment echoed throughout the studies included in this review.…”
Section: Implementation Of Ace Screeningmentioning
confidence: 99%
“…7 Adult patients with or without trauma history also felt that it was acceptable to be assessed for past trauma and expected their clinician would be able to help them. 20 Adult patients in a study by Flanagan et al 21 voiced acceptability, with over half of the respondents reporting that screening increased trust in their clinician, and 75% felt it helped their clinician know them better. Kalmakis et al 16 noted the positive association between ACE scores, chronic health conditions, and clinic visits and recognized that time spent addressing ACEs has the potential to affect patients' overall care.…”
Section: Acceptability Of Ace Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma-specific questions may also be emotionally invasive, triggering, and taxing to complete for some participants [41][42][43]. In contrast, some studies have noted that participating in research that assesses exposure to traumatic events is a neutral to positive experience for individuals who have experienced or are currently experiencing stress or adversity [43][44][45][46][47]. Given this mixed body of evidence, participants' willingness to respond to these measures is an important consideration in evaluating measures of adversity.…”
Section: Introductionmentioning
confidence: 99%
“…These professionals noted similar concerns and identified discomfort asking sensitive questions and worries about offending patients as additional barriers. Although past research has demonstrated that clinical screening for adversity is feasible, acceptable, and often supported by patients, parents, and providers [45,[54][55][56][57], it is not common practice. This observation highlights the need for screening methods that directly address these concerns yet allow for children's adversity to be easily assessed in clinical and primary care as well as in research settings.…”
Section: Introductionmentioning
confidence: 99%